Text and Context: Domestic Harmony and the Depiction of Hagar in Jubilees - Rothstein, David (2008)
The women of Genesis, and their depiction in both biblical and post-biblical sources, have been the focus of much scholarly activity. One beneficiary of this literary output is Jubilees, whose formulation of Israel's matriarchs and their relationships with their respective spouses reveals a systematic, and tendentious, reworking of the biblical material. This study focuses on Jubilees' presentation of Hagar, and demonstrates that, while not according her the same status as that granted Sarah and the other matriarchs, the work does portray her, and her relationship with Abraham, as enjoying a measure of importance not reflected in the biblical text.
Keywords: spousal; matriarchs; Marriage; Jubilees; Harmony; Hagar